These boys and their fathers : a memoir - Waters, Don, 1974- (University of Iowa Press, 2019)
"In 2010, Don Waters set out to write a magazine story about a surfing icon who'd known his absentee father. It was an attempt to find a way of connecting to a man he never knew. He didn't imagine that the story would become a years-long quest to understand a man who left behind almost nothing except for a self-absorbed autobiography for his abandoned son. Spindrift touches on Waters' boyhood with his single mother and her string of dysfunctional men, but it quickly expands into a gripping account of the life of a 1930's pulp writer, also named Don Waters, with whom Waters gets obsessed. This man and his wife raised a child on a sailboat during the Great Depression. This adventurous and picturesque vision of nuclear family life becomes more vivid to Waters than his own childhood. But as Don Waters delves deeply into this story--hiring an investigator to help him get to the bottom of the gaps--he winds up on the other side of fantasy, smack in the center of another family's hard truths. This wildly original book blends memoir, investigative reporting, and fiction to sort out difficult aspects of family, masculinity, and what it means to be a father. With striking honesty and empathy, Spindrift lays bare the daunting and messy task of finding meaning in an evasive world"--